Współczesna etnolingwistyka kognitywna – ludowa, narodowa, porównawcza? .......... 539 - Niebrzegowska-Bartmińska, Stanisława (Gwara i kultura w słowie zapisane: Księga jubileuszowa dedykowana Profesorowi Józefowi Kąsiowi, 2025)
MODERN COGNITIVE ETHNOLINGUISTICS: FOLK, NATIONAL, COMPARATIVE? Ethnolinguistics as a linguistic discipline studies the relationship between language and culture at two levels: folk language and folk culture, and standard language and national culture. Due to the subjective nature of ethnolinguistic research, the discipline is said to concern community identities, to be the key to the mentality and to the value system of a particular linguistic and cultural community. For some time now, three terms have been regularly used to refer to the scope of ethnolinguistic research: folk, national and comparative ethnolinguistics, the latter being identified with cross-national studies. The article identifies and systematically analyzes potential scopes of comparative ethnolinguistic research: a) folk vs. folk (comparison at the intra-linguistic and intra-cultural level); b) folk vs. national (comparison at the intra-linguistic and intra-cultural level); c) national vs. national (extra-linguistic and extra-cultural comparison); d) folk vs. folk (extra-linguistic and extra-cultural comparison). The analyses allow us to formulate the conclusion that systematically and methodically conducted descriptions and comparisons can reveal the “closeness” or “distance” of both historical and modern notions preserved in different languages and cultures. This serves as further evidence of the thesis that Polish traditional culture shares much in common with other Slavic folk cultures, and is more universal than Polish national culture.